Toward eradication: the effect of Mycobacterium bovis infection in wildlife on the evolution and future direction of bovine tuberculosis management in New Zealand - Livingstone, PG (N Z Vet J, 2015)
New Zealand's bovine tuberculosis (TB) control programme has greatly reduced the burden of tuberculosis on the farming industry, from 11% of mature cattle found with TB at slaughter in 1905 to <0.003% in 2012/13. New Zealand implemented TB control measures in cattle from the mid-twentieth century, and later in farmed deer. Control was based on established methods of tuberculin testing of herds, slaughter of suspect cases, and livestock movement control. Unexplained regional control failures and serious disease outbreaks were eventually linked to wildlife-vectored infection from the introduced Australian brushtail possum (Trichosurus vulpecula), which also triggered a wildlife disease complex involving a range of introduced species. This paper reviews the progressive elucidation of the epidemiology of Mycobacterium bovis in New Zealand's wildlife and farmed livestock, and the parallel development of research-led, multi-faceted TB control strategies required to protect New Zealand's livestock industries from damaging infection levels. The adoption of coordinated national pest management strategies, with increasingly ambitious objectives agreed between government and industry funders, has driven a costly but very successful management regime targeted at controlling TB in the possum maintenance host. This success has led to initiation of a strategy designed to eradicate TB from New Zealand's livestock and wildlife, which is considered a realistic long-term prospect.